Designing Language Teaching Tasks - Johnson K. Keith (New York, Palgrave Macmillan, 2003)
The book discusses issues of research methodology in a way which will be of interest to all students of applied linguistics. It is written in a clear and comprehensible style, and provides practical guidance on how to go about designing language teaching activities. As such it will be relevant to practising teachers and other professionals who need to write their own teaching tasks, or even modify already existing tasks for their students. Though the examples in the book deal with English as a foreign language, the content will be of interest to teachers of any foreign language.